RELATIONS BETWEEN ANOMIA AND VALUES OF THE INHABITANTS OF THE BALTIC STATES - Ļevina, Jeļena; Mārtinsone, Kristīne; Klince, Kristiāna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The purpose of this study was to determine the structure of anomia among the inhabitants of the Baltic states and to investigate whether there are relations between different dimensions of anomia and personal values. The secondary data from the European Values Study (EVS, 2008) were used. The sample consisted of the inhabitants of Latvia (n = 1506), Lithuania (n = 1500), and Estonia (n = 1518). For measurement of anomia and values questions from the original questionnaire of the EVS were used. In this study five components of anomia were found, namely, local social distrust, local social isolation, normlessness, global social distrust, and global social isolation. Numerous relations between anomia and values were found. It was found that there are the following common, similar patterns of relations between anomia and values of the inhabitants of Latvia, Lithuania and Estonia: (1) the importance of politics and religion is negatively associated with all dimensions of anomia (with one exception – there is no found the significant relation between the importance of religion and global social distrust in Latvia); (2) the importance of work and family is negatively associated with normlessness; (3) the importance of friends and acquaintances is negatively associated with global social distrust. Estonia was the only country for which it was found that the value of friends and acquaintances was negatively associated with global social isolation and the value of leisure time was negatively associated with local and global social distrust. The value of leisure time was positively associated with local social isolation in Lithuania and with normlessness in Latvia.